Analisis Etos Patos Dan Logos Dalam Ceramah Ustaz Abdul Somad Tentang Pentingnya Menjaga Akhlak - Wiji Rahayu; Rhani Febria (PT. Gudang Pustaka Cendekia, 2026)
This study aims to describe, identify, and analyze in depth the manifestation of ethos, pathos, and logos in Ustaz Abdul Somad's lecture on the importance of maintaining morals. The research method applied is a qualitative approach with a descriptive type to systematically outline linguistic facts and communication strategies. The data collection process relies on literature review techniques to gather trusted supporting scientific literature. Data reduction, data presentation, and conclusion drawing are utilized as analytical stages to dissect the entire lecture recording based on Aristotle's rhetorical triangle theory. The results show that the element of ethos or credibility is built through the adjustment of local sarong clothing, a humble attitude toward elders, respectful etiquette toward Madurese kiai, and authoritative hadith references. The element of pathos or emotional appeal is manifested through dramatic narratives of a mother's struggle in giving birth, the physical sacrifice of a father in the orchard, the story of his own mother's passing, and the analogy of an old Quranic mushaf for the elderly to arouse the congregation's pity and regret. The element of logos or logical argument is proven through the syllogism of moral priority over material wealth, the law of direct causal retribution for rebellious children, and textual historical proof regarding the inclusivity of the prophet's social relations with non-Muslims. The synchronization of these three rhetorical elements successfully packages weighty morality material into a logical yet deeply touching spiritual presentation for the congregation.